A filosofia política na Ciência Nova de Vico - Santos, Vanilda Honória dos (2012)
The objective of this dissertation is to examine the political philosophy of Giambattista Vico present in his greatest work named Scienza Nuova (1744) in which He looks into the common nature of the nations. The scienza nuova method is the cooperative relation between philosophy and philology highlighting the importance of the history for the political studies. The new proposal considers the field of practical life and human action in order to demonstrate that the origins of the nations as well as the natural law came from the common sense in the nations themselves.